Comparing the Workload Perceptions of Identifying Patient Condition and Priorities of Care Among Burn Providers in Three Burn ICUs. Issue 1 (January 2017) - McInnis, Ian; Murray, Sarah J.; Serio-Melvin, Maria; Aden, James K.; Mann-Salinas, Elizabeth; Chung, Kevin K.; Huzar, Todd; Wolf, Steven; Nemeth, Christopher; Pamplin, Jeremy C.
Abstract : Multidisciplinary rounds (MDRs) in the burn intensive care unit serve as an efficient means for clinicians to assess patient status and establish patient care priorities. Both tasks require significant cognitive work, the magnitude of which is relevant because increased cognitive work of task completion has been associated with increased error rates. We sought to quantify this workload during MDR using the National Aeronautics and Space Administration Task Load Index (NASA-TLX). Research staff at three academic regional referral burn centers administered the NASA-TLX to clinicians during MDR. Clinicians assessed their workload associated with 1) "Identify(ing) if the patient is better, same, or worse than yesterday" and 2) "Identify(ing) the most important objectives of care for the patient today." Data were collected on clinician type, years of experience, and hours of direct patient care. Surveys were administered to 116 total clinicians, 41 physicians, 25 nurses, 13 medical students, and 37 clinicians in other roles. Clinicians with less experience reported more cognitive work when completing both tasks ( P < .005). Clinicians in the "others" group (respiratory therapists, dieticians, pharmacists, etc.) reported less cognitive work than all other groups for both tasks ( P < .05). The NASA-TLX was an effective tool for collecting perceptions of cognitive workload associated with MDR. Perceived cognitive work varied by clinician type and experience level when completing two key tasks. Less experience was associated with increased perceived work, potentially increasing mental error rates, and increasing risk to patients. Creating tools or work processes to reduce cognitive work may improve clinician performance.